Profile religijności młodzieży prawosławnej w perspektywie badań socjologicznych = Profiles of religiosity among the orthodox church youth from the perspective of sociological research - Romanowicz, Wiesław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the dominant profiles of religiosity among the Orthodox Church youth in Poland. The characteristics of religiosity is based on the empirical data gathered by the author in the circles of the Orthodox Church youth. During the study conducted between 2009 and 2016 in the Lubelskie and Podlaskie Voievodships, the questionnaires prepared by the author were used. Together, in four studies, 800 respondents aged 17-25 and belonging to the Orthodox Church were involved. The study allowed identifying three profiles of religiosity among the Orthodox Church youth, i.e. traditional, reformatory and individualistic. Furthermore, the author draws attention to the growing religious awareness among this youth and to the role of religion in the process of self-identification.
Keywords: młodzież; prawosławie; religijność; youth; Orthdoox Church; religiosity